2014
DOI: 10.1097/md.0000000000000324
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up and Prognostic Factors for Advanced Thymic Carcinoma

Abstract: The aim of this study was to evaluate the long-term survival outcomes in patients with advanced thymic carcinoma and identify prognostic factors influencing the survival.We retrospectively analyzed 90 consecutive patients with pathologically confirmed advanced thymic carcinoma (Masaoka III and IV) in our institute, from December 2000 to 2012. Age, sex, clinical characteristics, laboratory findings, Masaoka and tumor node metastasis staging, pathologic grade, and treatment modalities were analyzed to identify p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
(55 reference statements)
4
15
0
Order By: Relevance
“…Our study indicated that distant metastasis was an independent prognostic factor for poor OS, and patients with lymph node metastasis alone had prolonged survival. This data agreed with the results of previous studies [2, 19]. …”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our study indicated that distant metastasis was an independent prognostic factor for poor OS, and patients with lymph node metastasis alone had prolonged survival. This data agreed with the results of previous studies [2, 19]. …”
Section: Discussionsupporting
confidence: 94%
“…Some studies have shown the prognostic value of positive lymph nodes [10, 20, 21], while other studies found no difference in survival based on their presence [2]. Park et al reported that dissection of more than 10 lymph nodes is required to predict prognosis accurately [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LDH has demonstrated to have prognostic significance in several tumors, including pancreatic cancer [2], lung cancer [3], advanced thymic carcinoma [4], osteosarcoma [5], renal cancer [6], prostate cancer [7], bladder cancer [8], and upper urinary tract transitional cell carcinoma (UUTTCC) [9]. Therefore, it is possible that serum LDH level may also represent a prognostic marker in patients with urinary system cancer.…”
Section: Introductionmentioning
confidence: 99%